Relationship between cerebral oxygenation, cardiac output, and blood pressure during transitional period in extremely low gestational age neonates - Deshpande, Poorva; Barbosa de Olivera, Caio; Jain, Amish; Hahn, Cecil; Shah, Prakesh S.; Guerguerian, Anne-Marie; McNamara, Patrick J. (Frontiers in Pediatrics, 2023)
Objective: To describe the relationship between cerebral oxygenation, cardiac output, arterial blood pressure (BP), and cerebral blood flow velocity in extremely low gestational age neonates (ELGANs) during transition. Methods: This study comprises secondary analyses from a prospective observational study conducted at a tertiary Neonatal Intensive Care Unit. Recruited ELGANs underwent cerebral saturation (CrSO2) monitoring and serial echocardiography during 72 hours from birth. Correlative analyses of CrSO2 and cerebral fractional tissue oxygen extraction (CFTOE) with left (LVO) and right ventricular output (RVO), superior vena cava (SVC) flow, middle cerebral artery blood flow mean velocity (MCA.MV), systolic (SBP), diastolic (DBP), and mean (MBP) BP were conducted. Results: Fifty ELGANs with median (range) gestational age of 25.9 (23.1 - 27.9) weeks were recruited. Echocardiography was performed sequentially at a median (range) age 5.0 (3.8 - 6.6), 17.3 (15.4 - 19.4), 31.0 (27.0 - 34.1), and 53.7 (49.3- 58.3) hours. RVO, LVO, CrSO2, and SBP increased over time but no changes in MBP, DBP, CFTOE, MCA.MV or SVC flow were noted. A weak correlation was identified between CrSO2 and SBP (r2 = 0.11, p = 0.047) and MBP (r2 = 0.12, p = 0.04) at 17.3 (15.4 - 19.4) hours. No correlation of either CrSO2 or CFTOE with any measures of blood flow was identified. Conclusion: There is a weak correlation between measures of cardiac output, BP, and MCA.MV with both CrSO2 and CFTOE in ELGANs during transition. Whether this finding suggests intact cerebral autoregulation requires prospective evaluation in a cohort of sick ELGANs.